O poder hegemônico das redes sociais: uma análise crítica do discurso de quem "vai pra rua" - Abella, Leticia Beatriz Gambetta (2017)
Social networks, in the context of the new Information and Communication Technologies (ICTs), have become a space of expression within the reach of all those who have access to the Internet. In Brazil, 49% of Brazilians have access to the internet, and within that number, 76% access every day. Twitter, Facebook, Instagram and various other participatory and interactive proposals arouse various communication interests that include personal exchanges of information and data, marketing announcements and various other purposes.One of the most important changes around the possibilities that the networks offer has arisen for those who want to win followers and defend a cause. Thus, social movements have found in these channels of expression a fertile ground of call and interactivity with their followers. This thesis has a purpose of analyze critically the discursive manifestations of the movement Vem pra rua on his Twitter and Facebook social networks, taking as a starting point the positioning of the group in its presentation on its official website. O Vem pra rua was born as a social movement in 2014 and according to what its own leaders express in the official page of the group, it is "a suprapartidary, democratic and plural movement that arose from the spontaneous organization of the civil society to fight for a Brazil best". The research is theoretically supported by the Sociological and Communicational Approach to Discourse (ASCD), the theoretical and methodological arm of the Critical Discourse Analysis (FAIRCLOUGH, 2001, 2003), which has its axis in interdisciplinary and transdisciplinary dialogue between (CID) (GUMUCIO-DAGRON, 2008, 2011), Multimodality (VIEIRA, 2015) and Functional Systemic Linguistics (LSF) (HALLIDAY, 2004).In the case of our work, we rely on the LSF Evaluation System as a tool for understanding the pathways of meaning construction that materialize in the current texts characterized by multisemiotic constructions. We have also consolidated our critical analysis with the Representation of Social Actors proposed by Teo Van Leeuwen (1997; 1008) that leads us to find the inclusion and exclusion marks in the forms chosen by the emitters to represent the actors in the text. This thesis seeks to understand, through the discourse manifested in the networks of the movement Vem pra rua, if the movement, as presented, has no partisan interests, if its articulation is based on spontaneous popular organization and if the media mobilization responds to democratic mechanisms of organization. Thus, following the methodological approach of a transdisciplinary approach, we find that the speech of presentation on the website of the movement is not a reflection of the identity construction that Vem pra rua has done in its social networks, particularly in the period before the impeachment of President Dilma. We conclude also that the new Information and Communication Technologies are potential tools of new ways of expression for minority groups, but, at the same time they are elements of great value to consolidate hegemonic groups with strong ideological interests too.